Word Order in Klamath - Sundberg, Karen (Kansas Working Papers in Linguistics, 1987)
Klamath, a Native American language of Oregon, has particularly "free" word order. Methods developed by Givon (1983) for the measurement of topic continuity, when applied to Klamath narrative texts, show that the position of NP's relative to the verb is not random, but determined by discourse-pragmatic factors.